Interstitial 1q23.3q24.1 deletion in a patient with renal malformation, congenital heart disease, and mild intellectual disability. Issue 9 (3rd June 2016) - Mackenroth, Luisa; Hackmann, Karl; Klink, Barbara; Weber, Julia Sara; Mayer, Brigitte; Schröck, Evelin; Tzschach, Andreas
Abstract : Interstitial deletions including chromosome region 1q23.3q24.1 are rare. Only eight patients with molecularly characterized deletions have been reported to date. Their phenotype included intellectual disability/developmental delay, growth retardation, microcephaly, congenital heart disease, and renal malformations. We report on a female patient with mild developmental delay, congenital heart disease, and bilateral renal hypoplasia in whom an interstitial de novo deletion of approximately 2.7 Mb in 1q23.3q24.1 was detected by array CGH. This is the smallest deletion described in this region so far. Genotype–phenotype comparison with previously published patients allowed us to propose LMX1A and RXRG as potential candidate genes for intellectual disability, PBX1 as a probable candidate gene for renal malformation, and enabled us to narrow down a chromosome region associated with microcephaly. © 2016 Wiley Periodicals, Inc.